Development of Automatic Identification System in Straitof Batam-Singapore - Koto, Jaswar; Amran, Nur Aireen (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
In Vessel Traffic System (VTS), AIS can detect a larger number of targets without considering the shadow effect and can provide more voyage information for port center.AIS can give full information such as types of ship, size, name, MMSI number and etc. AIS system is very important in the VTS to control ship in and out at the port area. This paper discussed on development of AIS system. The system was applied for safety purpose by taking ship tracking in Strait of Batam-Singapore.